2018
DOI: 10.1007/82_2018_109
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Bacteremic Escherichia Coli Strains: Evolution and Emergence of Drug-Resistant Pathogens

Abstract: In recent years, there have been several pandemics of E. coli strains which are highly virulent and antibiotics resistant. Here, we discuss one recent pandemic strain, ST131. These E. coli strains are members of the virulence-associated phylogenetic group B2 and exhibit extraintestinal virulence factors, including various adhesins, toxins, siderophores, and protectins. This group often also harbors a diverse range of antimicrobial resistance types and mechanisms and may have particular metabolic capacities tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 75 publications
0
17
0
Order By: Relevance
“…In this study, 16.7% ( n = 8) of isolates were ESBL producers and were positive for the presence of the bla CTXM gene. CTX-M enzymes have become the predominant ESBLs encountered in the clinic, and the rapid dissemination of ESBL is an alarming trend and is considered to be one of the world's main health threats (Yair and Gophna, 2018). It was previously reported that CTX-M-producing E. coli isolates often carry resistance to additional antibiotic classes, which can include co-trimoxazole, aminoglycosides, and fluoroquinolones (Pitout and Laupland, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, 16.7% ( n = 8) of isolates were ESBL producers and were positive for the presence of the bla CTXM gene. CTX-M enzymes have become the predominant ESBLs encountered in the clinic, and the rapid dissemination of ESBL is an alarming trend and is considered to be one of the world's main health threats (Yair and Gophna, 2018). It was previously reported that CTX-M-producing E. coli isolates often carry resistance to additional antibiotic classes, which can include co-trimoxazole, aminoglycosides, and fluoroquinolones (Pitout and Laupland, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, thymol was assessed as an agent to prevent planktonic and bacterial biofilm growth of L. monocytogenes, which is a major cause of foodborne disease [16] and E. coli, which is mainly a commensal microorganism, but many pathogenic strains have been detected in humans and animals [17]. In particular, twenty-five L. monocytogenes isolates from a variety of food samples and five reference strains were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of this E. coli lineage at the beginning of the 21 st century has been extensively studied, and associated with the progressive acquisition of fluoroquinolone and -lactam resistance (Price, et al, 2013). However, the very emergence of this lineage, might have preceded the acquisition of antibiotic resistance and the reasons for its success remains elusive (Kallonen, et al, 2017, Yair & Gophna, 2018. Similarly, K. pneumoniae clonal group 258 that expresses the carbapenemase KPC and is considered to be responsible for most infections by hospital-acquired carbapenem-resistant K. pneumoniae (Wyres & Holt, 2016).…”
Section: Population Level Analysis Imentioning
confidence: 99%